The leverage effect of bank disclosures - Philipp Johann König; Christian Laux; David Pothier (Deutsche Bundesbank, 2021)
The general view underlying bank regulation is that bank disclosures providemarket discipline and reduce banks' risk-taking incentives. We show that bankdisclosures can increase bank leverage and bank risk. The reason stems from theinteraction between insured and uninsured debt. Bank disclosures reduce the agencyproblem between uninsured debt and equity, thereby lowering the cost of leverage forbanks. By issuing uninsured short-term debt that is repaid ahead of insured depositswhen economic conditions deteriorate, banks dilute insured deposits. Higher levelsof uninsured short-term debt increase the subsidy provided by deposit insurance,which increases banks' risk-taking incentives. We identify conditions under whichthis negative leverage effect dominates the standard market discipline effect, so thatproviding market discipline through bank disclosures increases banks' risk.
Keywords: D80; G21; G14; 330; Bank Disclosures; Market Discipline; Bank Leverage